In Search for Canon of Singapore Malay Poetry: Reflection on Nature, Race, Religion and Love (Malay Literature, 2013)
This paper discusses selected poems by three generations of Malay writers in Singapore from the first generation poets who received their vernicular education during British colonial period, before Malayan Independence in 1957; to second generation writers who received Malay education when Singapore was part of Malaysia, 1957-1965 who established their poems in 1970s; and the third generation writers who received bilingual education who began to make impacts when Singapore become a Republic in 1980s. These iconic poems embody the easthetic as well as the cultural and political values of Malay society. It is an early attempt to define and search for canon of Singapore Malay poetry.Keywords: literature, canon, poetry, Singapore, culture, identity, values